Usage of Hypericum perforatum Microcapsules in the Production of Ayran (Drinking Yoghurt) - Fadime Seyrekoğlu; Hasan Temiz (Turkish Journal of Agriculture: Food Science and Technology)
H. perforatum, which is widely used in traditional medicine due to its bioactive compounds was extracted with ethanol-water (3:7). The extract was encapsulated with maltodextrin and gum arabic in a spray dryer in order to protect the phenolic compounds in its structure. Different amounts of microcapsules were added to our traditional drink, i.e. ayran (drinking yoghurt). The total phenolic content and DPPH radical scavenging activity of the microcapsules, extract of HP, and ayran samples were determined. The amount of total phenolic compounds in the microcapsule provided a superior effect than the extract. The ayran samples were supplemented with 2%, 3%, 4%, 5% and 6% of H. perforatum (HP) microcapsules and it is observed that total phenolic content (TPC) and DPPH radical scavenging activity indicated an increase with concentration. TPC and DPPH activity were determined as 256.94 mg GAE / 100mL and 78.05% for 6% of HP microcapsules supplemented samples. As a result of the sensory analysis, ayran samples which supplemented with 4% of HS microcapsule gained the highest scores by the panellists and received more appreciation than the control group. According to sensory analysis, HP4 (ayran produced with 4% HP added microcapsule) sample was determined as the best sample, while the HP6 (Ayran produced with 6% HP added microcapsule) sample had the highest scores in terms of DPPH scavenging activity and TPC results. The overall results of this study revealed that 4% HP supplemented ayran can be produced with its increased health benefits and desirable properties. In this study, the use of H. perforatum microcapsules in ayran, its effect on antioxidant and phenolic components, the usage rates and acceptability of microcapsules were investigated.